AN ANALYSIS ON ACCULTURATION BETWEEN ARABIC LANGUAGE AND JAVANESE LANGUAGE IN BULULAWANG, MALANG - Nanik Widayanti; Arining Wibowo; Trisno Tunggal Rahayu Wilujeng (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2015)
Acculturation is a process which is growth and appear if the society face with a new culture. And this new culture influence in their society, so they are adapting from the old culture become as new culture. Concerning with aculturation of islamic and javanese culture it is an interesting term, people not being aware to analyze something closer with their envinronment, something that not be watched and language is one of the interesting term to be anayze. Therefore, the researcher is interested in studying this problem by formulating three research problems: (1) what are the acculturaturation betweeen Arabis language and Javanese language in Bululawang?. (2) what are the meanings of those acculturation? (3) how the process of acculturation between Arabic language and Javanese language in Bululawang?. Hopefully of the findings of the acculturation between Arabic Language and Javanese language, people can catch the language philosophy, they know that some of language that they used is made from the acculturation. And for the younger generations must know well about the process from this acculturation, it can add more knowledge for them.